Exploration of change in persistence patterns of opioid use among patients with non-cancer and cancer pain over a three-year follow-up period - Abdullah Sani, Asween Rowena; Zin, Che Suraya; Mohamed, Abdul Hadi; Izat, Munira; Tan, Hung Ling; Ng, Kim Swan; Nissen, Lisa M.; Ng, Kim Swan (The Society of Hospital Pharmacists of Australia, 2019)
Background: Little is known about the different patterns of persistent opioid use and whether the patterns of clinical opioid use remain the same throughout the long-term opioid therapy. Aim: This study explores the different patterns of persistent opioid use and the change in these patterns over time in patients with non-cancer and cancer pain. Method: This retrospective cross-sectional study included patients with non-cancer and cancer pain receiving opioid prescriptions during 2013-2015 at outpatient tertiary hospital settings in Malaysia. A three-dimensional persistence measure consisting of treatment intensity, frequency and distribution were used to define persistent opioid users as wide (use opioids most of the days in a year), intermediate (use opioids daily) or strict (use opioids continuously to achieve a therapeutic concentration) users. The number of patients in each persistence definition and the change in persistence patterns over time was recorded. Results: Majority of persistent opioid users in the non-cancer and cancer groups were in the wide (9.3% vs.4.8%), followed by intermediate (3.1% vs.0.5%), and strict (1.8% vs.0.9%) definitions. Over a three-year study duration, change to a less stringent persistence definition was observed in the non-cancer group whereas no discernible pattern of change was observed in the cancer group. Conclusion: Change in the patterns of clinical opioid use over time was detected among persistent opioid users in both non-cancer and cancer groups using a three-dimensional persistence measure. This measure which is sensitive to the changes in clinical use of opioids over time can greatly impact future research and practices for better pain management involving opioids.